GlycA, a Novel Inflammatory Marker and Its Association With Peripheral Arterial Disease and Carotid Plaque: The Multi-Ethnic Study of Atherosclerosis. (September 2019) - Fashanu, Oluwaseun E.; Oyenuga, Abayomi O.; Zhao, Di; Tibuakuu, Martin; Mora, Samia; Otvos, James D.; Stein, James H.; Michos, Erin D.
GlycA, a composite biomarker of systemic inflammation, is associated with cardiovascular disease (CVD) and mortality, but its relationship with peripheral artery disease (PAD) is unknown. We assessed whether plasma GlycA is associated with ankle–brachial index (ABI), carotid plaque (CP), and incident clinical PAD among 6466 Multi-Ethnic Study of Atherosclerosis participants without CVD at baseline. GlycA, ABI, and CP were measured at baseline. Both ABI and CP were remeasured at 10 years. Incident clinical PAD was ascertained from hospital records. We used logistic, Cox, and linear mixed regression models adjusted for demographic and lifestyle factors. Mean (standard deviation, SD) was 62 (10) years for age and 381 (61) µmol/L for GlycA; 53% were women. GlycA was associated with both prevalent low ABI ≤0.8 (prevalence odds ratio [95% confidence interval, CI] per SD increment in GlycA, 1.65 [1.39-1.97]) and CP (1.19 [1.11-1.27]) at baseline. There were no significant associations of GlycA with incident low ABI, incident CP, or 10-year change in ABI or CP score. We identified 110 incident cases of PAD after 79 590 person-years. The hazard ratio (95% CI) of incident PAD per SD increment in GlycA was 1.38 (1.14-1.66). In conclusion, GlycA was associated with prevalent low ABI, prevalent CP, and incident PAD after a median of 14 years.